Effects of 8 weeks of combined strength and plyometric training on lower limb vertical stiffness and jump performance in elite long jump athletes - Xu, Z.; Sun, J.; Gu, J.; Yu, L. (Frontiers in Physiology, 2025)
Background: The approach run in the long jump relies heavily on lower limb vertical stiffness and elastic energy utilization (EEU). While conventional strength training enhances maximal force, it may not adequately improve stiffness or stretch-shortening cycle efficiency. Plyometric training (PT), by contrast, specifically targets these qualities. This study examined whether combining strength and plyometric training yields superior neuromuscular adaptations in elite long jump athletes.